SUSTAINABLE MENTAL HEALTH IN THE WORKPLACE: THE CRITICAL ROLES OF EMOTIONAL INTELLIGENCE AND WORKPLACE RESILIENCE - Jaggi, Nishtha; Gujral, Harminder Kaur (International Journal of Research -GRANTHAALAYAH, 2025)
The purpose of the present study is to analyse the impact of Emotional Intelligence and Workplace Resilience on Sustainable Employee Mental Health in corporate settings. A sample of 102 employees across industries was assessed using standardized questionnaires: the Wong and Law Emotional Intelligence Scale (WLEIS), the Connor-Davidson Resilience Scale (CDRISC), and the Job-related Affective Well-being Scale (JAWS). The results revealed a significant positive correlation between Emotional Intelligence and Sustainable Employee Mental Health (r = 0.465, p < 0.01). Similarly, Workplace Resilience demonstrated a positive correlation with mental health (r = 0.398, p < 0.01). However, regression analysis indicated that while Emotional Intelligence significantly predicted mental health (B = 0.870, p = 0.004), Workplace Resilience did not have a statistically significant predictive impact (B = 0.280, p = 0.265). These findings suggest that Emotional Intelligence plays a crucial role in enhancing employee well-being, whereas resilience alone may not be sufficient for sustaining mental health. The study emphasizes the importance of EI training and mental health support programs in organizations to foster a healthier and more resilient workforce. Further research is recommended to explore additional workplace factors affecting Sustainable Employee Mental Health.